The Genomic Consultation Service: A clinical service designed to improve patient selection for genome‐wide sequencing in British Columbia. Issue 4 (30th May 2018) - Elliott, Alison M.; du Souich, Christèle; Adam, Shelin; Dragojlovic, Nick; van Karnebeek, Clara; Nelson, Tanya N.; Lehman, Anna; ,; Lynd, Larry D.; Friedman, Jan M.
Abstract: Background: Access to clinical diagnostic genome‐wide sequencing (GWS; exome or whole genome sequencing) is limited in British Columbia. The establishment of a translational research initiative (CAUSES) to provide diagnostic genome‐wide sequencing for 500 children necessitated the development of a genomic consultation service, a clinical service established to provide consultation for physicians considering GWS for their pediatric patients throughout British Columbia. The Genomic Consultation Service provides patient‐specific genomic advice that may include: GWS, multi‐gene panel, single gene test, referral to medical genetics for clinical evaluation, or no genetic testing. Here, we describe and evaluate this service. Methods: We analyzed referral patterns, patient demographics, clinical indications, and genomic advice provided during the first year of this service. Comparison of outcomes from the first 6 months versus the last 6 months was performed. Results: A total of 407 referrals (238 males and 169 females [ p  = .0006]) were processed in the first year. Only children were eligible for referral and average patient age was 8 years. Medical genetics was the most frequent referring discipline, followed by biochemical disease and pediatric neurology, respectively. Most patients (68%) had syndromic intellectual disability. There was a significant difference in the frequency of referrals not appropriate for GWS in the first versus the second 6 months of the service (75/220 vs. 42/187; p  = .01) suggesting increasing awareness of testing criteria by referring physicians. Conclusion: This triage service is utilized throughout the province and appears to be an important factor in the high diagnostic rate (>40%) achieved in our GWS program. Abstract : The Genomic Consultation Service provides patient‐specific genomic advice that may include: genome‐wide sequencing, multi‐gene panel, single‐gene test, referral to Medical Genetics for clinical evaluation, or no genetic testing. Here, we describe and evaluate this service. This triage service is utilized throughout the province and appears to be an important factor in the high diagnostic rate (>40%) achieved in our genome‐wide sequencing program (CAUSES Research Clinic).